Stylistic and Cultural Problems Encountered in Translating Quranic Arabic Pun tawriya التورية into English: A Linguistic Contrastive Study - Abdelkarim, Majda Babiker Ahmed; Alhaj, Ali Albashir Mohammed (Technium Social Sciences Journal, 2023)
The translation is one of the most crucial and great cross-lingual and multicultural practices. One of these practices is the translation of Arabic puns into English in general and Quranic Arabic pun tawriya in particular which are the most vivid and sparkling parts of any tongue. Rendering Quranic Arabic pun tawriya into English increases many critical stylistic and cultural problems and challenges in renderings; these problems and challenges are attributable to the varying renditions of Arabic and English puns and the misunderstandings between the obvious references of a pun with obscure references, which could lead to a predetermined amount of ambiguity. This research paper assays to search stylistic and cultural problems confronted in translating Quranic Arabic pun tawriya التوريةinto English and to determine the translation procedures exerted in rendering the Quranic Arabic puns from Arabic into English. The study displayed translating the Quranic Arabic pun tawriya التوريةinto English and the equivalence of this Qur’anic Arabic pun is arduous and tricky. The results of the research paper also revealed that literal translation, zero translation, and a pun to non-pun translation are not always relevant and apt for rendering Quranic Arabic pun tawriya التوريةinto English because they have not efficiently maintained the dual meaning of the Qur’anic Arabic pun (QAP) into the Qur’an English pun (QEP).